2013
DOI: 10.1186/1746-1596-8-125
|View full text |Cite
|
Sign up to set email alerts
|

Subsequent intra-abdominal fibromatosis mimicking recurrent gastrointestinal stromal tumor

Abstract: Intra-abdominal fibromatosis (IAF) commonly develops in patients who had abdominal surgery. In rare instances, it occurs subsequent to gastrointestinal stromal tumor (GIST). This special situation has clinical significance in imatinib era. About 1000 patients with GIST in our institution from 1993 to 2010 were re-evaluated based on their clinical and pathological data, the treatment strategies and the follow-up information. We identified 2 patients who developed IAF after GIST resection. Patient 1 was a 54 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…It is critical to differentiate Desmoid tumors from GIST due to their different biological behavior and treatment methods. Although literature has observed an association between these two entities [ 16 , 18 , 23 ], they have different pathogenesis. Desmoid tumors can be easily mistaken for GIST as both tumors overlap in clinical presentation, morphology, and immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…It is critical to differentiate Desmoid tumors from GIST due to their different biological behavior and treatment methods. Although literature has observed an association between these two entities [ 16 , 18 , 23 ], they have different pathogenesis. Desmoid tumors can be easily mistaken for GIST as both tumors overlap in clinical presentation, morphology, and immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 ] Imatinib mesylate is a target-based molecule that is effective for both GIST and mesenteric fibromatosis that express c-kit . [ 7 , 16 , 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…The morbidity of GIST and mesenteric fibromatosis are both rare. [ 5 , 7 , 18 , 19 ] In the majority of cases, mesenteric fibromatosis occurred after the resection of GIST. [ 14 , 20 ] Thway et al [ 21 ] reported a case of intra-abdominal desmoid tumor after resection for GIST of the sigmoid mesocolon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been only two papers that reported individuals with both GIST and desmoid tumor (19,20). The coincidence of GIST and desmoid tumor is very rare.…”
Section: Discussionmentioning
confidence: 99%